Kindergarten Children’s Embarrassing Questions and Response’s Methods from Parents’ and Teachers’ Points of View - Alzahrani, maha; Fouad, Sama (Jordan Journal of Educational Sciences, 2025)
Objectives: The current study aims to identify the topics of kindergarten children’s embarrassing questions and response’s methods from parents’ and teachers’ points of view. Methodology: The research followed the descriptive approach using the questionnaire tool. The study sample included (203) parents and teachers of children in private kindergarten in the city of Jeddah. Results: The study results showed that the most embarrassing questions commonly asked by kindergarten children are questions asked about human creation. Conclusion: Based on the results, the study recommends raising parents and teachers’ awareness of the need to be keen on using diverse and appropriate parenting methods for children, which direct their thinking in the right ways and make them feel reassured to ask the questions that are in their minds. Keywords: children’s questions, embarrassing questions, gender differences, parents’ response methods, teachers’ response methods